2008
DOI: 10.17159/2413-3051/2008/v19i1a3314
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of a thermal power plant working on a Rankine cycle: A theoretical investigation

Abstract: Today, most of the electricity produced throughout the world is from steam power plants. However, electricity is being produced by some other power generation sources such as hydropower, gas power, bio-gas power, solar cells, etc. One newly devel-oped method of electricity generation is the Magneto hydro dynamic power plant. This paper deals with steam cycles used in power plants. Thermodynamic analysis of the Rankine cycle has been undertaken to enhance the efficiency and reli-ability of steam power plants. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Well-designed heat exchangers, hot and cold liquids flow with little pressure loss. Thermal energy from steam into mechanical energy through turbine turns, which runs a generator to produce electrical energy obtained from the Rankine Cycle as a system ( Figure 1) [9]. Efficiency thermal of ORC will be determined by equation 1 as follow :…”
Section: Organic Rankine Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Well-designed heat exchangers, hot and cold liquids flow with little pressure loss. Thermal energy from steam into mechanical energy through turbine turns, which runs a generator to produce electrical energy obtained from the Rankine Cycle as a system ( Figure 1) [9]. Efficiency thermal of ORC will be determined by equation 1 as follow :…”
Section: Organic Rankine Cyclementioning
confidence: 99%
“…To found the velocity value of fluid flow (9) Then the value of Reynold Numbers (10) To found the Nusselt Number value (11) To calculate convection coefficient inner and outer (12) To determine Thermal Resistance (R) and Overall heat transfer coeficient (U) (13) (14)…”
Section: Parameter Designmentioning
confidence: 99%
“…Steam is produced by heating the water with the help of heating sources, such as fossil fuel, nuclear heat energy, and solar heat energy. The steam generated spins a steam turbine that drives an electrical generator, thus producing electrical power that is then added to the grid through the main transformer [1][2][3]. Thermal power plants are becoming more successful due to technological advancements, and demand for them is increasing [4].…”
Section: Introductionmentioning
confidence: 99%
“…When applied to an entire Rankine cycle-based power plant, exergy analysis has revealed that the boiler is responsible for the greatest destruction of power generation capacity, rather than the condenser (which discharges the greatest amount of energy to the environment) [27]. Analysis of a Rankine cycle-based thermal power plant was presented by Kapooria et al [14], and an extensive overview of various energyand exergy-based efficiencies used in the analysis of power cycles was provided by Kanoglu et al [13].…”
Section: Introductionmentioning
confidence: 99%